Medieval Jews and the Christian past : Jewish historical consciousness in Spain and Southern France - Ben-Shalom, Ram (The Littman Library of Jewish Civilization in association with Liverpool University Press, 2015)
The focus in this book is on the historical consciousness of the Jews of Spain and southern France in the late Middle Ages, and specifically on their perceptions of Christianity and Christian history and culture. RamBen-Shalom offers a detailed analysis of Jews' exposure to the history of those among whom they lived. He shows that the Jews in these southern European lands experienced a relatively open society that was sensitive to and knowledgeable about voices from other cultures, and that this had significant consequences for shaping Jewish historical consciousness.